2021
DOI: 10.1101/2021.02.18.21251422
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Novel Olfactory Self-Test Effectively Screens for COVID-19

Abstract: Key to curtailing the COVID-19 pandemic are wide-scale testing strategies 1,2 . An ideal test is one that would not rely on transporting, distributing, and collecting physical specimens. Given the olfactory impairment associated with COVID-19 3-7 , we developed a novel measure of olfactory perception that relies on smelling household odorants and rating them online. We tested the performance of this real-time tool in 12,020 participants from 134 countries who provided 171,500 perceptual ratings of 60 different… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…33 An online olfactory tool for 12,020 participants from 134 countries indicated that their olfactory ratings were significantly correlated with the national COVID-19 infection rate in their countries over time. 28 Additionally, this real-time online tool showed considerable suggestive power at the individual level, with a sensitivity of 90% and specificity of 80%. 28 There was an independent and significant correlation between the viral clearance rate and the SST scores in COVID-19-induced anosmia patients, with a sensitivity of 79% and specificity of 87% (AUC = .883) for predicting viral clearance when the SST was >10.5.…”
Section: Anosmia As Predictive Toolmentioning
confidence: 95%
See 3 more Smart Citations
“…33 An online olfactory tool for 12,020 participants from 134 countries indicated that their olfactory ratings were significantly correlated with the national COVID-19 infection rate in their countries over time. 28 Additionally, this real-time online tool showed considerable suggestive power at the individual level, with a sensitivity of 90% and specificity of 80%. 28 There was an independent and significant correlation between the viral clearance rate and the SST scores in COVID-19-induced anosmia patients, with a sensitivity of 79% and specificity of 87% (AUC = .883) for predicting viral clearance when the SST was >10.5.…”
Section: Anosmia As Predictive Toolmentioning
confidence: 95%
“…28 Additionally, this real-time online tool showed considerable suggestive power at the individual level, with a sensitivity of 90% and specificity of 80%. 28 There was an independent and significant correlation between the viral clearance rate and the SST scores in COVID-19-induced anosmia patients, with a sensitivity of 79% and specificity of 87% (AUC = .883) for predicting viral clearance when the SST was >10.5. 34 Olfactory and gustatory dysfunctions were also associated with the prognosis of COVID-19 and were negatively associated with mortality in patients with an odds ratio of .26 (.15-.44).…”
Section: Anosmia As Predictive Toolmentioning
confidence: 95%
See 2 more Smart Citations
“…As such, based on the affordability of the different measures to tackle the pandemic, poorer countries, less likely to have the chance to be included in scientifically relevant large consortia, thus not necessarily receving wide amounts of money or not having the possibility to translate such funding into viable research frameworks, should adopt early screening strategies, relying on fast, useful biomarkers for infection detection, in turn being economically affordable. They could span from questionnaires about the quality of life of such people until home-based screening tools for side-effects, that might occur in the asymptomatic population even early during the infection process, therefore blocking the infection chain early [ 6 ].…”
Section: Investigationmentioning
confidence: 99%